Electroreduction of sulfur dioxide in some room-temperature ionic liquids - Barrosse-Antle, L; Silvester, D; Aldous, L; Hardacre, C; Compton, R (2008)
The mechanism of sulfur dioxide reduction at a platinum microelectrode was investigated by cyclic voltammetry in several room-temperature ionic liquids (RTILs) - [C2mim][NTf2], [C4mim][BF 4], [C4mim][NO3], [C4mim]-[PF 6], and [C6mim][Cl] where [C2mim] is l-ethyl-3- methylimidazolium, [C4mim] is l-butyl-3-methylimida-zolium, [C 6mim] is l-hexyl-3-methylimidazolium, and [NTf2] is bis(trifluoromethylsufonyl)imide - with special attention paid to [C 4mim][NO3] because of the well-defined voltammetry, high solubility, and relatively low diffusion coefficient of SO2 obtained in that ionic liquid. A cathodic peak is observed in all RTILs between -2.0 and -1.0 V versus a silver quasi-reference electrode. In [C4mim][NO 3], the peak appears at -1.0 V, and potential step chronoamperometry was used to determine that SO2 has a very high solubility of 3100 (±450) mM and a diffusion coefficient of 5.0 (±0.8) × 10-10 m2 s_1 in that ionic liquid. On the reverse wave, up to four anodic peaks are observed at ca. -0.4, -0.3, -0.2, and 0.2 V in [C4mim][NO3]. The cathodic wave is assigned to the reduction of SO2 to its radical anion, SO2-̇. The peaks at -0.4 and -0.2 V are assigned to the oxidation of unsolvated and solvated SO2-, respectively. The peak appearing at 0.2 V is assigned to the oxidation of either S2O 42- or S2O4-̇. The activation energy for the reduction of SO2 in [C4mim] [NO3] was measured to be 10 (±2) kJ mol-1 using chronoamperometric data at different temperatures. The stabilizing interaction of the solvent with the reduced species SO2-̇ leads to a different mechanism than that observed in conventional aprotic solvents. The high sensitivity of the system to SO2 also suggests that [C 4mim][NO3] may be a viable solvent in gas sensing applications. © 2008 American Chemical Society.